Creating presentations in MS Power Point - Megel, Yu. Ye.; Danylko, I. V.; Kovalenko, S. M.; Chaly, I. V.; Chala, O. I.; Mikhnova, O. D. (Kharkiv Petro Vasylenko National Technical University of Agriculture, 2016)
MS PowerPoint – is a versatile program that allows you to create presentations, consisting of a set of slides, which combines text with graphics, sound, photographs, images, video, and animation effects. Guidance will help students learn the practical techniques for working with the program.
Keywords: methodological guidelines; MS PowerPoint; information technology; presentations; software